Pengetahuan Masyarakat Tentang Protokol Kesehatan Dengan Tindakan Pencegahan Penularan COVID-19 Di Wilayah Kabupaten Sikka - Vianitati, Pasionista; Meo, Maria Yulita (Jurnal Keperawatan Muhammadiyah, 2021)
Objective:  The aim of this study to find out the relationship between public knowledge about health protocols and prevention measures for Covid-19 transmission in the Sikka Regency area.Methods:  This type of research is analytic observational with cross sectional design. A questionnaire was given to measure public knowledge about health protocols and an observation sheet to see the behavior of the community to prevent Covid-19 transmission. The sample in the study was 147 people using purposive sampling technique. Data analysis used Chi-Square with a significance level of α = 0.05.Results:  of this study were obtained public knowledge about the health protocol for the prevention of Covid-19 transmission was in a good category of 53.7% and most people made efforts to prevent Covid-19 transmission by 5M as much as 62.6%. And the results of statistical tests using the Chi Square test obtained pvalue = 0.029 <α = 0.05.Conclusion:  there is a significant relationship between public knowledge about health protocols and measures to prevent Covid-19 transmission in the Sikka Regency area. Therefore, all forms of health education to the public related to Covid-19 must continue to be carried out and carry out tiered evaluations related to the implementation of health protocols and it is hoped that the community will be more obedient to implementing health protocols to prevent Covid-19 transmission through 5M measures.